Old Boys Network in General Practitioners Referral Behavior - Franz Hackl; Michael Hummer; Gerald Pruckner (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2013)
We analyzed the impact of social networks on general practitioners (GPs) referral behavior based on administrative panel data from 2,684,273 referrals to resident specialists made between 1998 and 2007. To construct estimated social networks, we used information on the doctors place and time of study and their hospital work history. We found that GPs referred more patients to specialists within their social networks and that patients referred within a social network had fewer follow-up consultations and were healthier as measured by the number of inpatient days. Consequently, referrals within social networks tended to decrease healthcare costs by overcoming information asymmetry with respect to specialists abilities. This is supported by evidence suggesting that within a social network, better specialists receive more referrals than worse specialists in the same network.
Keywords: I1; I11; 330; Referral behavior; general practitioners; information asymmetry; social networks